Design of center-fed printed planar slot arrays. Issue 2 (9th December 2015) - Potgieter, L.; Joubert, J.; Odendaal, J. W.
Abstract : A design approach for printed planar slot array antennas is presented. The antenna array consists of half-wavelength slot radiators positioned on a rectangular grid, and a slotline feed network. Three planar slot array antennas for use in IEEE 802.11a applications are designed, a 2 × 2, a 2 × 4, and a 4 × 2 array, all radiating above an electric conductor ground plane placed a quarter-wavelength below the printed slots. These slot arrays have higher aperture efficiencies and occupy less space than typical microstrip patch arrays. The measured impedance bandwidths of the designed unidirectional slot arrays were 19.8, 15.3, and 16.7%, respectively, with peak gains of 11.7, 13.9, and 14.4 dBi. Measured results show very good agreement with the simulated results, which serves as validation of the array design procedure and the accuracy of the simulated results.